Analisis Pengembangan Kepariwisataan Desa Wisata Siboruon melalui Subsektor Kuliner di Desa Siboruon - Christien Christien; Liyus Waruwu; Denata Rajagukguk; Robert Juni Tua Sitio; Yulia K.S Sitepu (Journal of Innovative and Creativity, 2025)
This study aims to analyze the tourism conditions of Siboruon Tourism Village and explore its development opportunities through the culinary subsector. The research employed a qualitative descriptive approach using observation, in-depth interviews, and documentation, with data analyzed through SWOT analysis. The findings reveal that Siboruon Tourism Village holds significant potential to be developed as a tourist destination, primarily due to its natural beauty and cultural richness. These strengths serve as the main attraction for visitors, although the development process is still constrained by limited infrastructure, public facilities, and insufficient promotional efforts. Meanwhile, the culinary subsector demonstrates strategic value in supporting tourism growth. Local specialties such as Ayam Rias Siboruon, Otara Coffee, and Selai Toberu not only offer unique flavors but also represent the cultural identity of the community. These authentic culinary products can be developed into gastronomic tourism experiences and high-value souvenirs. The study concludes that the development of Siboruon Tourism Village requires collaborative strategies involving local government, business actors, and the community to strengthen its identity based on local potential in a sustainable manner.